1999
DOI: 10.1002/jlb.65.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the inducible NO synthase in human monocytic U937 cells allows high output nitric oxide production

Abstract: Nitric oxide (NO) produced by inducible NO synthase (iNOS, NOS-2) is an important component of the macrophage-mediated immune defense toward numerous pathogens. Murine macrophages produce NO after cytokine activation, whereas, under similar conditions, human macrophages produce low levels or no NO at all. Although human macrophages can express iNOS mRNA and protein on activation, whether they possess the complete machinery necessary for NO synthesis remains controversial. To define the conditions necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 73 publications
4
26
0
Order By: Relevance
“…Promastigotes of both species were used to infect human monocytic cell lines when in the stationary phase of growth. Human monocytic U937 cells (ATCC CRL-1593.2) [14], DFGiNOS U937 transfectant (clone 2), and pBABE U937 vector control transfectant were maintained in culture as previously described [11]. For infection with Leishmania, these cells were differentiated for 3 days at 5 ϫ 10 5 cells/mL in Dulbecco's modified Eagle's medium (DMEM) 10% fetal calf serum (FCS) containing 10 -7 M 1,25-dihydroxy-vitamin D 3 (VD3; Calbiochem) and 10 -7 M retinoic acid (RA; Sigma), in the absence of geneticin for all cell lines; lipopolysaccharide (LPS; from Escherichia coli 0:55-B.5, Difco Laboratories; 1 µg/mL) was added for the last 12-15 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Promastigotes of both species were used to infect human monocytic cell lines when in the stationary phase of growth. Human monocytic U937 cells (ATCC CRL-1593.2) [14], DFGiNOS U937 transfectant (clone 2), and pBABE U937 vector control transfectant were maintained in culture as previously described [11]. For infection with Leishmania, these cells were differentiated for 3 days at 5 ϫ 10 5 cells/mL in Dulbecco's modified Eagle's medium (DMEM) 10% fetal calf serum (FCS) containing 10 -7 M 1,25-dihydroxy-vitamin D 3 (VD3; Calbiochem) and 10 -7 M retinoic acid (RA; Sigma), in the absence of geneticin for all cell lines; lipopolysaccharide (LPS; from Escherichia coli 0:55-B.5, Difco Laboratories; 1 µg/mL) was added for the last 12-15 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture supernatants were assayed for NO 2 Ϫ by incubating them with Griess reagents as described elsewhere [11]. Absorbance was measured at 550 nm using a 690-nm reference filter.…”
Section: Measurement Of No 2 ϫ and O 2 ϫmentioning
confidence: 99%
See 2 more Smart Citations
“…10 These data strongly suggest that the factors that regulate iNOS expression differ between mice and humans and this has been supported by studies in which it has been shown that activation of iNOS in human monocytes/macrophages is relatively refractory to lipopolysaccharide and cytokine activation, and comparatively little is known about the regulation of this enzyme in these cells. 11,12 However, iNOS can be readily induced in human cell types of varying lineages by a combination of cytokines, and in human fetal astrocytes activation by IL-1 in combination with IFN-␥ forms a potent inducing stimulus. 13 Because IL-1 and IFN-␥ are known to be up-regulated in active MS lesions, these data would suggest that astrocytes should be activated to express iNOS at these sites.…”
mentioning
confidence: 99%